Association between QTc interval prolongation and outcomes of diabetic foot ulcers: Data from a 4-year follow-up study in China. (April 2018) - Wang, Shumin; He, Yang; Xu, Lei; Zhang, Shanshan; Gu, Xueming; Gu, Junyi; Shi, Jianyuan; Shen, Yaping; Tang, Zhengyi
Highlights: QTc prolongation was related with higher all-cause or cardiovascular mortality in DFU patients. QTc prolongation was an independent risk factor of cardiovascular mortality in DFU population. QTc interval was not associated with wound healing, recurrence and NCCVE in DFU patients. Abstract: Objectives: To examine whether QTc interval prolongation is an independent risk factor of outcomes in patients with diabetic foot ulcers (DFU). Research design and methods: 331 patients with type 2 diabetes and DFU hospitalized in a Chinese tertiary hospital were recruited. ECG was done at baseline and QTc interval was calculated through Bazett's formula. Participants were classified into 2 groups according to the QTc interval as prolonged (≥440 ms) or not (<440 ms). These patients were followed-up for an average of 48 months to observe the outcomes, including ulcer healing, ulcer recurrence, nonfatal cerebral or cardiovascular events (NCCVE), cerebral cardiovascular death, cardiac death and all-cause death. The associations between the risk of outcomes and QTc interval prolongation, as well as per 1-SD increase in QTc interval were analyzed by Cox proportional-hazards models. Results: In terms of the univariate Cox proportional hazard models, patients with QTc interval prolongation had a higher all-cause mortality (HR = 1.621, 95%CI: 1.040–2.526, P = .013), higher cardiac mortality (HR = 2.011 95%CI: 1.106–3.657, P = .019), higher cerebral cardiovascular mortality (HR = 1.525, 95%CI: 0.8151–2.852, P = .045). The multivariate analysis showed that QTc prolongation was an independent risk factor for cardiac death (HR = 5.465, 95%CI: 2.818–8.112, P = .039). Similar results were obtained when QTc interval was used as a continue variable, a 1-SD increase in QTc interval was associated with an 5.883 times risk for cardiac mortality (HR = 6.883, 95%CI: 4.153–9.613, P = .012). The association between QTc interval prolongation with ulcer healing, recurrence and NCCVE were not observed either in univariate or multivariate analysis (P > .05). Conclusion: QTc interval prolongation was a plausible predictor for cardiac death in DFU patients, but it cannot accurately predict ulcer healing or recurrence.